2016
DOI: 10.1007/s11701-016-0576-x
|View full text |Cite
|
Sign up to set email alerts
|

Early impact of robot-assisted partial nephrectomy on renal function as assessed by renal scintigraphy

Abstract: To measure the early impact of robot-assisted partial nephrectomy (RAPN) on renal function as assessed by renal scan (Tc 99m-DTPA), addressing the issue of risk factors for ischemic damage to the kidney. All patients undergoing RAPN for cT1 renal masses between June 2013 and May 2014 were included in this prospective study. Renal function as expressed by glomerular filtration rate (GFR) was assessed by Technetium 99m-diethylenetriaminepentaacetic acid (Tc 99m-DTPA) renal scan preoperatively and postoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Patients with larger T1a tumors were more likely to develop CKD in the present study; but, stratification by nephrectomy type (Figure ) indicated that this positive association was present only for patients managed with PN. This is concordant with previous reports evaluating kidney functional changes using renal scintigraphy after PN . To ensure negative surgical margins, the amount of functional parenchyma removed during PN is determined by tumor size and complexity, whereas that is not the case with RN.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with larger T1a tumors were more likely to develop CKD in the present study; but, stratification by nephrectomy type (Figure ) indicated that this positive association was present only for patients managed with PN. This is concordant with previous reports evaluating kidney functional changes using renal scintigraphy after PN . To ensure negative surgical margins, the amount of functional parenchyma removed during PN is determined by tumor size and complexity, whereas that is not the case with RN.…”
Section: Discussionsupporting
confidence: 90%
“…This is concordant with previous reports evaluating kidney functional changes using renal scintigraphy after PN. 38,39 To FIGURE 2 Associations between selected factors and new-onset chronic kidney disease (CKD) stratified by nephrectomy type. Adjusted odds ratios (OR) and 95% confidence intervals (CI) estimated using logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the ischemia technique, 32 studies used main renal artery clamping [ 8 10 , 12 , 14 17 , 19 , 20 , 25 28 , 32 36 , 40 , 41 , 42 , 46 49 , 51 , 52 , 54 , 56 , 57 , 58 ], 5 studies selective ischemia [ 21 24 , 30 ], 5 studies used both main renal artery and selective ischemia [ 37 , 38 , 43 , 45 , 53 ], 8 studies compared global ischemia and the off- clamp technique [ 11 , 13 , 18 , 29 , 31 , 39 , 50 , 55 ], and 1 study selective ischemia and the off-clamp technique [ 44 ]. Across the included trials, 42 studies used warm ischemia during the enucleoresection [ 8 15 , 17 , 19 24 , 26 34 , 36 45 , 47 50 , 53 , 54 , 55 , 58 ], while 2 trials utilised cold ischemia with iceball [ 35 , 52 ]; 8 studies used both the cold and warm ischemia [ 15 , 16 , 18 , 25 ...…”
Section: Resultsmentioning
confidence: 99%
“…Percentual eGFR variation was estimated in 49 studies, at a mean of 11.6 months of follow-up; values ranged from 0.7% to 37.1%, with a mean value of 12.5%. Fourteen studies reported percentual change of IRF on renal MAG- 3 scintigraphy [ 9 , 14 , 19 , 20 , 22 , 24 , 39 , 40 , 41 , 45 , 47 , 52 , 54 , 58 ]. At a mean follow-up of 7.9 months, IRF changes varied from 1.9% to 28%, with a mean IRF decrease of 13.3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation